CYLD Promotes TNF-α-Induced Cell Necrosis Mediated by RIP-1 in Human Lung Cancer Cells - Xing Lin; Qianshun Chen; Chen Huang; Xunyu Xu (Mediators of Inflammation)
Lung cancer is one of the most common cancers in the world. Cylindromatosis (CYLD) is a deubiquitination enzyme and contributes to the degradation of ubiquitin chains on RIP1. The aim of the present study is to investigate the levels of CYLD in lung cancer patients and explore the molecular mechanism of CYLD in the lung cancer pathogenesis. The levels of CYLD were detected in human lung cancer tissues and the paired paracarcinoma tissues by real-time PCR and western blotting analysis. The proliferation of human lung cancer cells was determined by MTT assay. Cell apoptosis and necrosis were determined by FACS assay. The results demonstrated that low levels of CYLD were detected in clinical lung carcinoma specimens. Three pairs of siRNA were used to knock down the endogenous CYLD in lung cancer cells. Knockdown of CYLD promoted cell proliferation of lung cancer cells. Otherwise overexpression of CYLD induced TNF-α-induced cell death in A549 cells and H460 cells. Moreover, CYLD-overexpressed lung cancer cells were treated with 10 μM of z-VAD-fmk for 12 hours and the result revealed that TNF-α-induced cell necrosis was significantly enhanced. Additionally, TNF-α-induced cell necrosis in CYLD-overexpressed H460 cells was mediated by receptor-interacting protein 1 (RIP-1) kinase. Our findings suggested that CYLD was a potential target for the therapy of human lung cancers.